Properties of the Magellanic Corona - Scott Lucchini; Elena D’Onghia; Andrew J. Fox (The Astrophysical Journal, 2024)
We characterize the Magellanic Corona, the warm gaseous halo around the Large Magellanic Cloud (LMC). The Corona is a key ingredient in the formation of the Magellanic Stream and has recently been observed in high-ion absorption around the LMC. In this work, we present a suite of high-resolution hydrodynamical simulations to constrain its total mass and temperature prior to the infall of the Magellanic Clouds to our Galaxy. We find that the LMC is able to host a stable Corona before and during its approach to the MW through to the present day. With a Magellanic Corona of >2 × 10 ^9 M _⊙ at 3 × 10 ^5 K, our simulations can reproduce the observed total mass of the neutral and ionized components of the Trailing Stream, the size of the LMC disk, the ionization fractions along the Stream, the morphology of the neutral gas, and the on-sky extent of the ionized gas. The Corona plays an integral role in the survival, morphology, and composition of the Magellanic Clouds and the Trailing Stream.